KAJIAN HAK KEPEMILIKAN PROPERTI OLEH WARGA NEGARA ASING DI INDONESIA - Asa Aulia; Dedi Hantono (Universitas Batam, 2021)
In developing the Indonesian state, a large amount of money is required. One of the financing comes from investment or capital invested by foreign parties with an investment permit of 30-60 years. The impact of this period causes foreigners to need housing facilities that can support their activities and streamline their business in the context of PMA. In response to these conditions, the government issued Government Regulation No. 41/1996. Based on such regulatory conditions, foreigners generally get a house by renting. This allows foreigners to apply for a rental period of more than 10 years for Indonesians who own the house. However, in practice there are many houses whose conditions, room arrangement, layout, environment, or so on do not suit the tastes of foreigners. In addition, the condition of ownership of property on a lease basis also prevents foreigners from being able to renovate space. According to the UUPA, foreigners are not allowed to own HGB and can only obtain usage rights. This needs to be revised to adapt to the current and more dynamic investment climate conditions. In other countries the right to use property reaches 99 years. The proposal to extend the right to use housing for foreigners will contribute foreign exchange for the country.